Adult child educational attainment and older parents' psychosocial outcomes during the COVID-19 pandemic - Karla Renata Flores Romero; Yulin Yang; Sharon H. Green; Sirena Gutierrez; Erika Meza; Jacqueline M. Torres (BMC, 2024)
Abstract Background Older adults' psychosocial outcomes during the COVID-19 pandemic have been inequitable by socio-economic status (SES). However, studies have focused solely on own SES, ignoring emerging evidence of the relationship between adult child SES and late-life health. We evaluated whether adult child educational attainment - a core marker of SES - is associated with older parents' psychosocial outcomes during the pandemic. Methods We used data from the Survey of Health, Aging, and Retirement in Europe (SHARE) 2004-2018 and the SHARE Corona Surveys (SCS) 2020 and 2021. We included 40,392 respondents ≥ 65 years who had pre-pandemic information on adult child educational attainment and self-reported psychosocial outcomes during the pandemic, including self-assessments of worsened psychosocial outcomes compared to the pre-pandemic period. We used generalized estimating equations with a Poisson distribution and a log link, adjusted for respondent and family-level characteristics, including respondents' own educational attainment. Results Older adults whose adult children averaged levels of educational attainment at or above (vs. below) their country-specific mean had a lower prevalence of feeling nervous (Prevalence Ratio [PR]: 0.94, 95% Confidence Interval [CI]: 0.90, 0.97), sad or depressed (PR: 0.94, 95% CI: 0.91, 0.98), and having sleep problems (PR: 0.94, 95% CI: 0.90, 0.97) during the pandemic. Additionally, higher adult child educational attainment was associated with a lower risk of perceiving worsened feelings of nervousness (PR: 0.95, 95% CI: 0.90, 1.01) and worsened sleep problems (PR: 0.91, 95% CI: 0.82, 1.01) as compared to the pre-pandemic. In stratified models, protective associations were observed only in countries experiencing "high" levels of COVID-19 intensity at the time of the survey. All of these results are derived from adjusted models. Conclusions Adult child SES may have "upward" spillover effects on the psychosocial wellbeing of older parents during periods of societal duress like the pandemic.